RISE: Adaptive strategies for microbial performance through optimization approach / Assoc. Prof. Dr Khalilah Abdul Khalil - Abdul Khalil, Khalilah (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
Microbial bioprocessing represents an essential part of biotechnological applications.